Where next for design research? Understanding research impact and theory building. (May 2020) - Cash, Philip
Abstract : Research impact and theory development are major challenges facing design research. However, the nature of these challenges and how they should be addressed is a controversial question. Here, this question is addressed via a systematic analysis of research published in Design Studies, which delivers three contributions: demonstrating the explanatory and predictive power of theory development for research impact; showing that theory development has broken down in design research; offering a theoretical 'landscape' of design research, which is used to provide an evidence-based agenda for future theory development. It is proposed that these contributions resolve much of the controversy surrounding theory development and its value, and point the way forward for a theory development revolution in design research. Highlights: Empirically analyses theory development and research impact in design research. Demonstrates the predictive power of theory development for research impact. Shows that theory development has broken down in design research. Proposes a theoretical 'landscape' of design research, and six key insights. Provides an evidence-based agenda for future theory development in design research.